Temporal trends and outcomes in ST-segment elevation myocardial infarction: a cardiac magnetic resonance imaging study over the course of 15 years. (3rd October 2022) - Lechner, I; Reindl, M; Tiller, C; Holzknecht, M; Fink, P; Troger, F; Mayr, A; Klug, G; Bauer, A; Reinstadler, S J; Metzler, B
Abstract: Aims: Development of evidence-based treatments in ST-elevation myocardial infarction (STEMI) patients during the last 30 years have been associated with improved outcome; however, there are data suggesting a plateauing since around 2008 (1). Moreover, contemporary data are very scarce regarding the temporal trends of infarct outcomes. This study sought to describe the temporal trends in infarct severity at myocardial tissue level over the course of 15 years by means of cardiac magnetic resonance imaging (MRI). Methods: This study analyzed STEMI patients treated with percutaneous coronary intervention (PCI) in our Medical University who underwent a cardiac MRI between 2005 and 2021. The 15-year study period was divided into sequential 2-years blocks. Infarct characteristics were measured using MRI at 3 days [IQR 2–5] after PCI. Results: A total of 844 STEMI patients (17% female) with a median age of 57 (interquartile range [IQR]: 51–66) years were included. The rate of evidence-based treatments was high for aspirin (99%), P2Y12i (99%), beta-blockers (91%), ACEi/ATi (92%) and statins (100%) and did not change significantly over the study period (p>0.05) with the exception for ACEi/ATi (p=0.03) and prasugrel (p<0.001), which increased and clopidogrel, which decreased during the study course (p<0.001). TIMI risk score did not change over the study period (p=0.43). Overall median infarct size was 16 [9–25]% and did not change (p=0.39) significantly. MVO, a marker of severe reperfusion injury, was also comparable (p=0.16). Accordingly, LV ejection fraction remained virtually unchanged (p=0.23) Conclusion: Although further implementation of evidence-based treatments was seen also during the last 15 years, there has been no effect on infarct size, reperfusion injury and LV ejection fraction for patients who undergo primary PCI due to STEMI. Novel treatment strategies are needed to address this unmet therapeutic need. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Austrian Science Fund (FWF)Austrian Society of Cardiology